The Influence of Tax Payer Compliance on Tax Revenue Moderated by Tax Audit - Yanuar, Salwa Shabuha; Maslichah, Maslichah; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2024)
This research aims to analyze the effect of taxpayer compliance on tax revenues which is moderated by tax audits at KPP Pratama Singosari. This research was conducted using a quantitative approach with a questionnaire as the research instrument. The research sample in this study was 130 taxpayers using a sampling technique using the Slovin formula and purposive sampling method. Data analysis was carried out using moderated regression analysis using the SmartPls version 4 program. The research results show that taxpayer compliance has a significant effect on tax revenue. Tax audits do not have a significant effect on tax revenues. However, tax audits can moderate taxpayer compliance with tax revenues. The results of this research are expected to develop a theory of compliance for taxpayers and help monitor the results of existing policies. It is also hoped that the research results can provide insight or material for implementing compliance theory in social life, especially for taxpayers.Keywords: Taxpayer compliance, tax revenue, tax audit.